Analyzing the Administrative Burden of Competency Based Medical Education. Issue 2 (May 2022) - Cheung, Kevin; Rogoza, Christina; Chung, Andrew D.; Kwan, Benjamin Yin Ming
Purpose: Postgraduate residency programs in Canada are transitioning to a competency-based medical education (CBME) system. Within this system, resident performance is documented through frequent assessments that provide continual feedback and guidance for resident progression. An area of concern is the perception by faculty of added administrative burden imposed by the frequent evaluations. This study investigated the time spent in the documentation and submission of required assessment forms through analysis of quantitative data from the Queen's University Diagnostic Radiology program. Methods and Materials: Data regarding time taken to complete Entrustable Professional Activities (EPA) assessments was collected from 24 full-time and part-time radiologists over a period of 18 months. This data was analyzed using SPSS to determine mean time of completion by individuals, departments, and by experience with the assessment process. Results: The average time taken to complete an EPA assessment form was 3 minutes and 6 seconds. Assuming 3 completed EPA assessment forms per week for each resident (n = 12) and equal distribution among all staff, this averaged out to an additional 18 minutes of administrative burden per staff member over a 4 week block. Conclusions: This study investigated the perception by faculty of additional administrative burden for assessment in the CBME framework. The data provided quantitative evidence of administrative burden for the documentation and submission of assessments. The data indicated that the added administrative burden may be reasonable given mandate for CBME implementation and the advantages of adoption for postgraduate medical education.